Conceptual Analysis of the Student Teams Achievement Division (STAD) Model in Islamic Religious Education Learning - Fathinah Mufidah; Nia Wardhani; Yusnaini Yusnaini (Jurnal Ilmiah Guru Madrasah, 2026)
This study aims to provide a conceptual analysis of the Student Teams Achievement Division (STAD) learning model in the context of Islamic Religious Education (IRE). The method employed is a literature review using a conceptual analysis approach of relevant sources, including books, academic journals, and previous research findings. The analysis focuses on the theoretical foundations, characteristics, implementation procedures, as well as the strengths and limitations of the STAD model in IRE learning. The findings indicate that the STAD model has significant potential to enhance student engagement, promote collaborative learning, and improve understanding of religious concepts through constructive social interaction. Furthermore, the implementation of STAD aligns with Islamic values such as cooperation (ta’awun) and togetherness. However, its effectiveness largely depends on teacher readiness, classroom management, and student characteristics. Therefore, appropriate implementation strategies are required to optimize the use of the STAD model in Islamic Religious Education.